2018
DOI: 10.1016/j.jvb.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Personality characteristics of male and female executives: Distinct pathways to success?

Abstract: It is widely believed that female and male leaders have fundamentally different characteristics and styles, which are thought to explain why organizations with more gender-diverse top management teams perform somewhat better. Unfortunately, few studies have concretely specified such differences or examined whether men and women in leadership roles, particularly executives, indeed differ on core psychological characteristics such as personality traits. Drawing on three alternative perspectives on the roles of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 82 publications
1
61
0
Order By: Relevance
“…Therefore, boards are likely to have a good sense of a (potential) CEO's level of extraversion. Additionally, executive roles require more agentic characteristics relative to lower‐level leadership positions (Hunt, Boal and Sorenson, 1990; Wille et al ., 2018). Hence, extraversion may be viewed as particularly important by boards for upper echelon positions, where CEOs are expected to be highly active, competitive and unwavering in decisions (e.g.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Therefore, boards are likely to have a good sense of a (potential) CEO's level of extraversion. Additionally, executive roles require more agentic characteristics relative to lower‐level leadership positions (Hunt, Boal and Sorenson, 1990; Wille et al ., 2018). Hence, extraversion may be viewed as particularly important by boards for upper echelon positions, where CEOs are expected to be highly active, competitive and unwavering in decisions (e.g.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…This finding was consistent with the finding by Türetgen et al (2008) that the personality characteristic of dominance and self-efficacy did not predict emergence to leadership. Similarly, Wille et al (2018) revealed that personality traits namely;…”
Section: Discussionmentioning
confidence: 98%
“…Further, the finding of the study was inconsistent with Türetgen et al (2008) who established that the personality characteristic of self-monitoring (locus of control) predicted leader emergence. Likewise, Wille et al (2018) revealed that female executives tended to demonstrate an archetypical "leader personality" focused on assertiveness,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations